Integrasi Artificial Intelligence dalam Pembelajaran Sains di Pendidikan Menengah: Sebuah Tinjauan Literatur - Nissa Ul Awal; Nurmalahayati Nurdin (Institut Teknologi Garut, 2026)
The rapid advancement of digital technology has opened opportunities for the use of artificial intelligence (AI) in learning, particularly in science education, which requires an understanding of complex concepts. This study aims to examine the development of research and the implementation of AI in science learning at the secondary education level (junior and senior high schools or equivalent). The method employed is a Systematic Literature Review (SLR) using the PRISMA approach on 41 scientific articles published between 2020 and 2025. The results indicate a significant increase in the number of research publications related to AI in science education, with physics as the most dominant field, followed by general science, chemistry, and biology. The most widely studied types of AI include educational chatbots, interactive simulations and videos, AI-based learning analytics, adaptive learning systems, as well as virtual reality and augmented reality (VR/AR) technologies. Overall, the findings show that the application of AI has a positive impact on student learning outcomes, learning motivation, learning personalization, and assessment effectiveness. However, this review also identifies several major challenges, including infrastructure limitations, low digital literacy among educators, and ethical and data protection issues. This study provides an overview of research trends and implications for educational policy and future research related to the integration of AI in science learning at the secondary education level.